2017
DOI: 10.3892/ol.2017.7502
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin increases apoptosis of colon cancer cells through targeting Janus kinase 2/signal transducer and activator of transcription 3 signaling

Abstract: Abstract. As a derivative of artemisinin, dihydroartemisinin is effective in the treatment of malaria. Dihydroartemisinin has been identified to possess inhibitory effects in numerous types of animal model with tumors, indicating that it has an antineoplastic effect. The aim of the present study was to analyze the potential anticancer effects of dihydroartemisinin, particularly its effect on apoptosis of colon cancer cells. In the present study, it was identified that dihydroartemisinin inhibited cell viabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…40 Furthermore, sustained induction of the JAK2/STAT3 pathway is highly correlated to tumorigenesis, proliferation, apoptosis and metastasis of tumors, including CC. 41 While PTK6 overexpression might induce the expression of STAT3 and proliferation of breast cancer cells. 42 In addition, miR-214 modulated CC procession through c-Met sialylation via the JAK2/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…40 Furthermore, sustained induction of the JAK2/STAT3 pathway is highly correlated to tumorigenesis, proliferation, apoptosis and metastasis of tumors, including CC. 41 While PTK6 overexpression might induce the expression of STAT3 and proliferation of breast cancer cells. 42 In addition, miR-214 modulated CC procession through c-Met sialylation via the JAK2/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Dihydroartemisinin has been found to have potent cytotoxic and proapoptotic activity by suppressing activated JAK2/STAT3 signals. It also suppressed downstream targeted proteins in the human tongue (Cal-27), colon (HCT-116), liver (HepG2) as well as head and neck (FaDu) carcinoma cell lines [217,218].…”
Section: Dihydroartemisininmentioning
confidence: 99%
“…Artemisinin exhibited the ability for selectively inhibiting cancer cells but only minimal cytotoxicity to normal cells (Li X. et al, 2018). Most notably, DHA, a derivative of artemisinin with better water solubility, has shown potent effects on cell growth inhibition and apoptosis induction by significantly inhibiting Jak2/STAT3 signaling activation and downstream target proteins in human head and neck cancer FaDu, liver cancer Hep-G2, colon cancer HCT-116, and tongue cancer Cal-27 cells (Jia et al, 2016; Wang D. et al, 2017). Moreover, a study showed that DHA at the concentration of 20 µM induced transient activation of JNK in human umbilical vein endothelial cells (Dong et al, 2016).…”
Section: Anticancer Tcms Through Targeting Jak-stat3 Signal Pathwaymentioning
confidence: 99%